Odpowiedzi

Najlepsza Odpowiedź!
2009-11-12T16:40:45+01:00
A) (m + n)(m-2)+(m-n)(m+1) = m² - 2m +mn - 2n + m² + m - mn - n = 2m² - m- n
b) (3x-2)(3x-2y+1)-4x(2x-3y+1) = 9x² - 6xy + 3x - 6x + 4y - 2 - 8x² + 12xy - 4x = x² + 6xy - 7x + 4y - 2
c) 3(m+1)(n-2)+2(n+1)(m-2) = 3mn - 6m + 3n - 6 + 2mn - 4n + 2m - 4 = 5mn - 4m - n - 10
d) x(x+1)(x+2)-x(x-1)(x-2) = x³ + 2x² + x² + 2x - x³ + 2x² +x² - 2x = 6x²
2009-11-12T16:41:04+01:00
A) =m^2-2m+nm-2n+m^2+m-nm-n=2m^2-2m-3n
b) =9x^2-6xy+3x-6x+4y-2-8x^2+12xy+4x=x^2+6xy+x+4y
c) =3(mn-nm+n-2)+2(nm-2n+m-2)=3n-6+2nm-4n+2m-4=-n+2m+2nm-10
d) x(x^2+2x+x+2)-x(x^2-2x-x+2)=x^3+2x^2+x^2+2x-x^3+2x+x^2-2x=3x^2+2x

^ to potęga jakby ktoś nie wiedział.